O que é ser pai hoje?: Reflexões sobre as mudanças da paternidade. - Silva, Rafael Matias da (2023)
This research investigates the meanings of fatherhood and how social, historical, political, and economic changes interfere in the role of the man-father, causing changes in his functions and images. The choice for this theme arose from the need to better understand the configurations of being a father today, since fatherhood is still little explored in Psychology studies and seems to conflict with the traditional way of exercising fatherhood, in which a distant father is revealed emotionally, provider and dictator of the law at home. In the meantime, the general objective of this research is: to reflect what it is to be a father today, identifying the changes of fatherhood. Our study uses a qualitative approach, characterized as exploratory. For that, we carried out a bibliographical survey on the subject in question, focusing on gender studies and paternity, within the scope of Psychology and Human Sciences and gender studies, to identify the changes that have occurred in our society. Therefore, our data collection is classified as bibliographical, surveying works that deal with the theme of fatherhood. The method used in this research is hypothetical-deductive, since we start from a question arising from a social problem to which we seek to answer based on theories and authors already consecrated by the sciences. The analyzes of this research showed us that, in recent years, studies on paternity have intensified, mainly from the 1980s onwards. We consider changes in the family scope, understanding that the family has also been changing, especially in recent centuries. With the decline of patriarchy, the man-father was faced with several transformations, and had to watch his power fall, losing his role as provider and spokesman of the law. The feminist movement and the LGBT+ movement contributed to the role and place of the father- man undergoing a major change when realizing the growth of women's active participation in the public and private space. The conclusion is that fatherhood, previously marked by the presence of a provider father, cold and distant, who held power over his family members, goes through a transition process in which new care practices are required of this man-father within the family nucleus. Furthermore, we understand that fatherhood should be read as plural, multifaceted and interrelated with several other social phenomena, such as family, gender, technological advances, political-economic and cultural context, and subjectivities.